2011
DOI: 10.2478/v10176-011-0012-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in total active centres on particle surfaces during coal pyrolysis, gasification and combustion

Abstract: In the paper, on the basis of our studies and the available literature data, a model of changes in the number of active centers corresponding to the structure of the reactive coal particle has been developed. A new distribution function that links the specific surface area of a particle with its porosity and reaction degree has been proposed. An equation for estimation of changes in this parameter during the reaction, on the basis of the initial value, has been presented. In the range of our data and the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The pore volume and surface area are mainly contributed by the pores with a diameter between 2 and 10 nm. [ 49 ] More interestingly, pores with size between 2 and 3 nm dominate all four samples, indicating that all these samples are mesoporous carbons. Comparing the FS without acid etching to other samples, it can be proved that the acid etching process generates more pores effectively, thereby increasing the surface area.…”
Section: Resultsmentioning
confidence: 94%
“…The pore volume and surface area are mainly contributed by the pores with a diameter between 2 and 10 nm. [ 49 ] More interestingly, pores with size between 2 and 3 nm dominate all four samples, indicating that all these samples are mesoporous carbons. Comparing the FS without acid etching to other samples, it can be proved that the acid etching process generates more pores effectively, thereby increasing the surface area.…”
Section: Resultsmentioning
confidence: 94%
“…The analysis range and resolution of the microscopic region were 1 μm and 1 cm −1 , respectively. 29 Combined with the proximate analysis, ultimate analysis, and AFT of the samples, the results showed that the DCLR had less volatile content, and the ash content is 21.40%. The objective amplification was 50 times.…”
Section: Physicochemical Structurementioning
confidence: 93%
“…The developed pore structure provided more active sites and facilitated the gasification reaction. 29 Combined with the proximate analysis, ultimate analysis, and AFT of the samples, the results showed that the DCLR had less volatile content, and the ash content is 21.40%. When pyrolysis was carried out at 1300°C, the ash had melted, so it mainly appeared as large cracks after pyrolysis in the particles.…”
Section: Physicochemical Structurementioning
confidence: 93%
“…19,21 The number of active centers is related to the internal surface area and porosity of particles. 23 Breakdown of C H contributes to the formation of C active sites. 24 The active sites usually exist at the crystallite edges of macropores and mesopores of char.…”
Section: Introductionmentioning
confidence: 99%